Pengaruh Keteladanan Guru Pendidikan Agama Kristen Terhadap Tingkah Laku Siswa Kelas XI SMA Negeri 1 Sipoholon Kabupaten Tapanuli Utara Tahun Ajaran 2023/2024 - Cindy Monika Sirait; Ronny Simatupang; Dorlan Naibaho (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to determine the positive and significant influence of the example of Christian Religious Education Teachers on the Behavior of Class XI Students of SMA Negeri 1 Sipoholon, North Tapanuli Regency, Academic Year 2023/2024. The method used is an inferential descriptive quantitative research method, with a population of 228 students and a sample taken of 20% so that the research sample is 46 students using the Random Sampling technique. The instrument used in this research uses a closed questionnaire of 30 questions, of which 15 questionnaire items are for variable X and 15 items are for variable Y which have been tested on 35 students outside the research sample. The results of the research show that there is a positive and significant influence between the example of Christian Religious Education Teachers on the Behavior of Class XI Students at SMA Negeri 1 Sipoholon, North Tapanuli Regency, Academic Year 2023/2024. 1) Test the relationship between rcount > rtable, namely 0.630 > 0.291; 2) Significant test tcount>ttable, namely 5.381>2.021; 3) The determination test is 39.69%, 4) The regression equation is obtained from Y ̂= 23.62+0.50X; 5) Test the hypothesis using the F test to obtain Fcount > Ftable = (α= 0.05, dk numerator k = 11, dk denominator = n-2 = 46 - 2 = 44) namely 28.66 > 2.08. Thus Ha, that is, there is a positive and significant influence between the example of Christian Religious Education Teachers on the Behavior of Class